ENCAPSULATION OF SOYBEAN SEEDS WITH Actinomycetes AS A BIOCONTROL AGENT AGAINST Sclerotium rolfsii Sacc - Masnilah, Rachmi; Anam, Khairul; Pradana, Ankardiansyah Pandu (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2024)
This study evaluates the effectiveness of Actinomycetes in encapsulating soybean seeds to control damping-off disease caused by Sclerotium rolfsii. With national soybean demand reaching 22 million tons per year and domestic production only 1 million tons, increasing production is essential. One major constraint is the attack of plant pathogens such as S. rolfsii, which can cause significant losses. Actinomycetes were isolated from the rhizosphere of weeds and tested for their antagonistic activity in vitro. Seed encapsulation using various carriers (kaolin, talc, and zeolite) was conducted to determine the most effective formula. In vivo tests showed that the Actinomycetes isolate PM2 exhibited the best antagonistic activity, with the zeolite formulation reducing pre-emergence damping-off disease incidence to 12.50% and post-emergence damping-off to 8.25%, compared to the positive control. These results indicate that the use of Actinomycetes in soybean seed encapsulation is an effective and sustainable method for controlling damping-off disease. Zeolite as a carrier proved to provide a supportive environment for antagonistic microbes, maintaining moisture and supplying necessary nutrients. This research reveals the great potential of Actinomycetes as a biocontrol agent in plant disease management strategies, which can significantly enhance soybean production and support national food security.